2016
DOI: 10.1002/pros.23227
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Prostate Stromal Cell Induced by Benign Prostatic Hyperplasia Epithelial Cell Stimulated WithTrichomonas vaginalisvia Crosstalk With Mast Cell

Abstract: The inflammatory mediators released by BPH epithelial cells in response to infection by trichomonads induce the migration and activation of mast cells. The activated mast cells induce the proliferation of prostate stromal cells via CXCL8-CXCR1 and CCL2-CCR2 signaling. Our results therefore show that the inflammatory response by BPH epithelial cells stimulated with T. vaginalis induce the proliferation of prostate stromal cells via crosstalk with mast cells. Prostate 76:1431-1444, 2016. © 2016 Wiley Periodicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 50 publications
5
66
0
Order By: Relevance
“…We previously reported that CCL2 produced by T. vaginalis infection in vaginal epithelial cells induced the migration of mast cells . Moreover, our in vitro study showed that mast cells were involved in the proliferation of stromal cells caused by inflammation of prostate epithelial cells stimulated with T. vaginalis . In the present in vivo model, we noted increased numbers of mast cells and degranulated mast cells in the prostate tissues infected with T. vaginalis (Figures and ).…”
Section: Discussionsupporting
confidence: 69%
“…We previously reported that CCL2 produced by T. vaginalis infection in vaginal epithelial cells induced the migration of mast cells . Moreover, our in vitro study showed that mast cells were involved in the proliferation of stromal cells caused by inflammation of prostate epithelial cells stimulated with T. vaginalis . In the present in vivo model, we noted increased numbers of mast cells and degranulated mast cells in the prostate tissues infected with T. vaginalis (Figures and ).…”
Section: Discussionsupporting
confidence: 69%
“…There are recent reports of a high infection rate (21.2%) of Tv in patients with chronic recurrent prostatitis and urethritis in Korea, and a high detection rate (34%) of Tv in benign prostatic hyperplasia (BPH) tissue . We showed previously that Tv stimulation of prostatic epithelial and stroma cells in vitro induced an inflammatory response through the production of chronic inflammatory cytokines, such as interleukin (IL)‐1β, IL‐6, and C‐X‐C motif ligand 8 (CXCL8), which there are high levels in the seminal fluid of patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CCPS) …”
Section: Introductionmentioning
confidence: 99%
“…4,5 We showed previously that Tv stimulation of prostatic epithelial and stroma cells in vitro induced an inflammatory response through the production of chronic inflammatory cytokines, such as interleukin (IL)-1β, IL-6, and C-X-C motif ligand 8 (CXCL8), which there are high levels in the seminal fluid of patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CCPS). [6][7][8][9][10] Inflammation has been implicated as a carcinogen in a number of human cancers, and in a number of organs, 11,12 and a variety of epidemiological and histopathological findings have suggested that prostate cancer (PCa) risk is correlated with inflammation. 13 The pathogenesis of PCa involves multiple genes as well as environmental factors, such as diet and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms by which it may contribute to these conditions include: (a) adherence to and lysis of prostate epithelial cells; (b) induction of intra‐prostatic inflammation and cytokine production; (c) inhibition of prostate epithelial cell apoptosis; and (d) upregulation of proto‐oncogenes . More recently, T. vaginalis has also been observed to increase prostate cell line proliferation and invasiveness, has been detected in prostate tissue from men with BPH, and has been found to be associated with the presence of BPH, as well as later prostate cancer risk and aggressiveness in some, but not all, sero‐epidemiologic studies.…”
Section: Introductionmentioning
confidence: 99%
“…These suggestive findings may be relevant for prostate condition development because higher early-to mid-life PSA concentrations have been found to predict greater prostate cancer risk later in life. 1,2 More recently, T. vaginalis has also been observed to increase prostate cell line proliferation and invasiveness, 3,4 has been detected in prostate tissue from men with BPH, 2,5 and has been found to be associated with the presence of BPH, 6 as well as later prostate cancer risk and aggressiveness in some, 7,8 but not all, [9][10][11][12][13][14] sero-epidemiologic studies.…”
mentioning
confidence: 99%